New procedures for controlling the ivory trade - Rowan Martin (Pachyderm)
The author's report dealing with elephant population estimates, a method for setting quotas and the administrative procedures for both international and internal management which would be required to make the quota system work is summarized. The key aspects include a country's setting of a quota for tusks expected to be exported in 1986, a complete registration of all stocks (both producer and consumer states), the setting up of an ivory unit in the CITES Secretariat and a set of referral procedures for clearance by the importing country